Exceptional point singularities in multi-section DFB lasers. (1st May 2022) - Shahmohammadi, Mehran; Süess, Martin J; Peretti, Romain; Kapsalidis, Filippos; Forrer, Andres; Beck, Mattias; Faist, Jérôme
Abstract: A laser exhibits both controllable gain and loss and, under proper design conditions, is an ideal non-Hermitian system allowing the direct observation and engineering of spectral singularities such as exceptional points (EPs). A dual section distributed feedback (DFB) quantum cascade laser (QCL) is a prototype of such a system, allowing the controlled coupling of a ladder of cavity Fabry–Perot modes to a quarter wave shifted DFB mode. Tuning the coupling strength and the gain difference between these two set of modes enables probing the regimes from weak coupling to strong coupling and the robust observation of EP singularities. At these EPs, the laser exhibits a sequence of lasing and switching off the coherent emission when pumped above transparency. Additionally, the pumping scheme allows the deliberate lifting of the EP degeneracy. These results show that dual section QCL is a perfect platform to study EPs because the coupling parameter and system loss can be tuned in a single device.